Health benefits of having more female classmates: Quasi-experimental evidence from China. (December 2022) - Guo, Yuhe; Li, Shaoping; Chen, Siwei; Tang, Yalin; Liu, Chengfang
Abstract: We investigate the impact of having more female classmates on students' physical health outcomes. To do so, we draw on panel data from the first two waves of the China Education Panel Survey (CEPS) and take advantage of exogenous variation in classroom gender composition brought by the random assignment of students to classes when they entered junior high school. Results from the value-added model show that having more female classmates helps to improve the physical health outcomes of junior high school students in China. Specifically, a one-percentage-point (pp) increase in the proportion of female classmates in Grade 7 explains a 0.003-0.004 pp increase in one's probability of staying normal BmiAZ or going from abnormal to normal BmiAZ, a 0.029-0.031 increase in the BmiAZ score of those with low starting BmiAZ, a 0.003 increase in one's HAZ score, and a 0.157-0.165% or 0.166-0.177% decrease in the diopter of one's left or right lens of glasses from Grade 7 to Grade 8, respectively. One possible mechanism underlying these relationships is that more female classmates bring healthier behaviors. Heterogeneity analyses indicate that the beneficial effects of having more female classmates on health outcomes are more prominent among boys, students with less-educated parents, and those attending rural schools or schools with bigger class sizes.